A comprehensive analysis of cotton VQ gene superfamily reveals their potential and extensive roles in regulating cotton abiotic stress - Chen, Pengyun (BMC Genomics, 2020)
BACKGROUND: Valine-glutamine (VQ) motif-containing proteins play important roles in plant growth, development and abiotic stress response. For many plant species, the VQ genes have been identified and their functions have been described. However, little is known about the origin, evolution, and functions (and underlying mechanisms) of the VQ family genes in cotton. RESULTS: In this study, we comprehensively analyzed the characteristics of 268 VQ genes from four Gossypium genomes and found that the VQ proteins evolved into 10 clades, and each clade had a similar structural and conservative motif. The expansion of the VQ gene was mainly through segmental duplication, followed by dispersal. Expression analysis revealed that many GhVQs might play important roles in response to salt and drought stress, and GhVQ18 and GhVQ84 were highly expressed under PEG and salt stress. Further analysis showed that GhVQs were co-expressed with GhWRKY transcription factors (TFs), and microRNAs (miRNAs) could hybridize to their cis-regulatory elements. CONCLUSIONS: The results in this study broaden our understanding of the VQ gene family in plants, and the analysis of the structure, conserved elements, and expression patterns of the VQs provide a solid foundation for exploring their specific functions in cotton responding to abiotic stresses. Our study provides significant insight into the potential functions of VQ genes in cotton. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12864-020-07171-z.